Testicular biopsy with Tru-Cut needle in conjunction with fibrin adhesive or nylon suture: assessment of post-biopsy testicular function in rams - Sartori, R.; Prestes, Nereu Carlos [UNESP]; Canavessi, AMO; Curi, P. R.; Bergfelt, D. R. (Elsevier B.V., 2002)
Testicular biopsy has been a complementary technique for clinical and research purposes to evaluate reproductive function in males. However, hemorrhage, inflammation, degeneration, and adhesion are factors that might limit the use of this procedure. In order to minimize these potential problems, fibrin glue derived from snake venom, a tissue adhesive with sealing, hemostatic, and healing properties, was used in conjunction with bilateral testicular biopsy with the Tru-Cut needle and was compared with a more conventional technique that uses nylon suture. Thirty mature rams were randomly assigned to three groups of 10 animals each, as follows: nonsurgical control group (no scrotal surgery, or biopsy); biopsy + glue group (fibrin glue on puncture sites and skin incisions) and biopsy + suture group (compression with swab on puncture sites and suturing of skin incision). The surgeries of the rams in the biopsy groups were performed on the same day, which was designated Day 0 for all three groups. Data of scrotal circumference, number of spermatozoa per ejaculum, percentage of morphologically abnormal spermatozoa, spermatozoa motility, and serum testosterone concentrations from Days -7, 20, 40, 60, 80 and 100 were evaluated. There were no significant differences between groups within days for any of the parameters evaluated. In conclusion, the testicular biopsy procedure using the Tru-Cut needle in conjunction with conventional nylon suture or the more novel fibrin glue in rams did not affect any of the parameters of testicular function evaluated in this study and was shown to be relatively simple, safe and efficient. (C) 2002 Published by Elsevier B.V. B.V.
Keywords: testicular biopsy; ram; fibrin adhesive; semen; testosterone